Life Cycle Engineering and Management of Products: Theory and Practice - de Oliveira, José Augusto [UNESP]; Lopes Silva, Diogo Aparecido; Puglieri, Fabio Neves; Barrera Saavedra, Yovana María (Springer Nature, 2021)
This book presents the role of life cycle engineering and life cycle management of products and services and their contributions to corporate environmental sustainability and the circular economy. It addresses the main techniques, tools, systems and practices for improving the environmental performance of business products and services throughout their life cycles. The book covers the main topics and concepts related to life cycle engineering and life cycle management applied to the business context. It presents the themes through basic and in-depth theories. In addition, all chapters provide examples of real and hypothetical case studies for discussion and assimilation of theoretical content and its contextualization in the real and practical business scenario. The chapters are complemented by quantitative exercises.
Keywords: Circular Economy; Circularity; Environmental Performance; Environmental Sustainability; Life Cycle Engineering